Profile, treatment patterns, and influencing factors of anthracycline use in breast cancer patients in China: A nation‐wide multicenter study. (2nd September 2021) - Guo, Fengzhu; Yi, Zongbi; Wang, Wenna; Han, Yiqun; Yu, Pei; Zhang, Su; Ouyang, Quchang; Yan, Min; Wang, Xiaojia; Hu, Xichun; Jiang, Zefei; Huang, Tao; et al.
Abstract: Background: Anthracycline‐based chemotherapy (ABC) is one of the standard therapies against breast cancer. However, few guidelines are currently available to optimize the use of ABC. Therefore, the present analysis aimed at determining the profile and treatment patterns of ABC and the association of clinicopathological characteristics with ABC selection. Methods: We retrospectively analyzed the data of a nation‐wide multicenter epidemiological study, which collected the medical records of breast cancer patients receiving chemotherapy in different settings from seven geographic regions in China (NCT03047889). Results: In total, 3393 patients were included, with 2917 treated with ABC. Among them, 553 (89.8%), 2165 (81.7%), and 814 (25.7%) were subjected to ABC as neoadjuvant, adjuvant, and advanced chemotherapy, respectively. The most frequently used regimens were anthracycline‐taxane‐based combinations for neo‐ and adjuvant chemotherapy, along with taxanes and oral fluorouracils for the palliative stages. In the overall cohort, patients aged < 40 or 40‐65 ( p < 0.001), in premenopause ( p < 0.001), without comorbidities ( p = 0.016), with invasive ductal carcinoma ( p = 0.001), high lymph node involvement ( p < 0.001), in the pTNM stage II, III, or IV versus stage I ( p < 0.001), subjected to mastectomy ( p < 0.001) or subjected to sentinel lymph node biopsy combined with axillary lymph node dissection ( p = 0.044), or with a decreased disease‐free survival ( p < 0.001) were more likely to be recommended to ABC. Conclusion: Taken together, ABC remained the mainstay of breast cancer treatment, especially in neo and adjuvant therapy. ABC was mainly used as a combination therapy, and the correlation between influencing factors and ABC choice varied during different settings, indicating the preference and different perspectives of medication considered by medical oncologists regarding the use ABC in China. Abstract : The nation‐wide study revealed that anthracycline‐based chemotherapy (ABC) remained the mainstay of breast cancer treatment, especially in neo and adjuvant therapy, and was predominantly used as a combination therapy. The correlation between clinicopathological characteristics and ABC choice varied at different settings, suggesting the preference and different perspectives of medication regarding the use ABC in China. The real‐world data contribute to guide the selection of the appropriate treatment and maximize the benefit of chemotherapy for patients.